Chronic Pulmonary Aspergillosis with Tracheobronchial Involvement - Hermawan, Yosua Kevin; Pranata, Anak Agung Ngurah Satya; Putra, Wayan Wahyu Semara; Sunaka, I Wayan; Novitasari, Novitasari; Angelina, Cokorda Rio (Jurnal Respirasi, 2024)
Introduction: Aspergillosis is a fungal infection commonly found in human lungs and takes several forms. Chronic pulmonary aspergillosis (CPA) commonly affects individuals with underlying disease, most usually lung tuberculosis (TB). Aspergillosis can cause the formation of a fungus ball in the lung cavity and can also manifest in the tracheobronchial area, although this is rarely seen in immunocompetent patients. Case: A 23-year-old woman came with persistent cough, hemoptysis, and shortness of breath for 4 months. The patient also had a significant weight loss and a history of lung TB 3 years ago. She had completed her lung TB medication. Physical examination showed increased respiratory rate and rhonchi on the left lung. GeneXpert showed no Mycobacterium tuberculosis (MTB) detected. The chest X-ray showed a cavity on the left superior lobe of the lung. Bronchoscopy showed multiple plaques along the trachea, carina, and left main bronchus. A chest computed tomography (CT) scan with contrast enhancement was performed, and a fungus ball was found inside the cavity in the left upper lobe of the lung. The patient was given intravenous fluconazole as therapy and continued with oral fluconazole when discharged. A second bronchoscopy was performed, and improvement was shown. Conclusion: Early detection and treatment should be applied to CPA patients since some studies showed poor prognosis and low five-year survival rates.